Implementasi Peraturan Daerah Nomor 3 Tahun 2009 Tentang Pengelolaan Sampah di Kabupaten Jepara - Paramita, Yustisia Prajna; Marom, Aufarul; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The implementation of the waste management policies in the county of jepara referring to perda no 3 in 2009, waste management policies in the county of jepara is government program in order penanggulangan pileup of rubble produced by people and their own in the activities of the reduction and waste management. Â The process of the implementation of the waste management policies in the county of jepara not separated from a factor that supports and hinder. Based on the theory of a van metter, van horn and edwards iii factor that supports and hinder keputusan standart policy, and the target the structure of the bureaucracy, resources, the disposition and communications.For the implementation of the policy of waste management in the county of jepara uses the method research qualitative descriptive in nature.With research site district jepara, in the region of and respondent government apparatus, covering janitor and city people and uses the technique research interview deep, documentation and observationFactor inhibitors of existing in the implementation of the waste management in the county of jepara are the reduction and waste management which is has not yet been optimal, standart and target a policy that only the outlines course, the structure of the bureaucracy that is less effective, still lack of resources and pengkomunikasian a less well on the purpose of the implementation of the waste management from the government to the public.